Sistem Pakar Diagnosis Tingkat Stres Berbasis Android dengan Metode Certainty Factor - Noviandi Noviandi; Diah Aryani; Arief Ichwani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The number of cases of Corona Virus Diesis (COVID-19) according to the World Health Organization (WHO) is 93,217,287 people. In the case of Covid-19, one of which is making changes in behavior is education. The teaching and learning process has changed into bold learning in the education sector. Students who continuously carry out the learning process at home can increase stress because previous research data stated that the level of severe anxiety experienced by students was one of them caused by daring learning, which reached 95.59%, and students reached 97.69%. This research aims to develop an expert system for dealing with stress in high school students. The method used for making the expert system is the Certainty Factor. Based on functionality testing using black box testing, it shows that all components produce the expected and appropriate results, then for accuracy testing using a confusion matrix through a comparison between manual calculations and system calculations, so that the accuracy test results are 100%. Therefore, the expert system for diagnosing stress diseases in high school students can be said to be feasible.